Meta-analysis Study of Achievement Motivation and Academic Achievement - Atanasius Emillio Gary Waluyohadi (Universitas Katolik Soegijapranata, 2019)
Academic achievement becomes something important for students. Academic achievement has a relationship with achievement motivation. Based on the results of a review of the literature, there is an inconsistency in the results of research on the relationship of academic achievement with achievement motivation. Therefore, the author conducted a meta-analyst with a significant effect size correlation with academic achievement (r = 0.334508) and significant with CI (0.170255; 0.480675). The results of the I2 statistical test showed a high inconsistency with a value of 98.7%. There is also high heterogeneity in the results of this meta-analysis with the value of Cohcran Q showing 1,029.604289. The relationship between the two variables also shows the bias by looking at the results of the egger, which is 9.311441. The results of statistical tests show that achievement motivation and academic achievement have a fairly high effect size correlation. The heterogeneity in this meta-analysis is high and there is publication bias.